(untitled) (JONAH : Journal of Nursing and Homecare, 2024)
Hallucinations are states in which the individual perceives something which is false. Auditory hallucinations are the state of an individual hearing voices or whispers that aren’t actually there, the contents of auditory hallucinations can be in the form of sounds that contain orders that cause the patient to follow these orders so that the patient can injure himself or those around him, or just noise that causes the patient to be restless. In January 2023 there were 91 patients, with hallucination nursing problems totaling 74 people (81.3%) in the Kuantan Room. The aim of this research is to describe psychiatric nursing care for clients with auditory hallucination problems at the Tampan Hospital in Riau Province. This research was conducted specifically in the Kuantan Room with two research subjects, namely Mr. R and Mr. I. Nursing care was carried out from 5 to 11 April 2023. This study used interview and observation techniques. The results showed that there was a change in the symptoms of hallucinations in the research subjects, subject I Mr. R symptoms have not appeared so that it has been allowed to be outpatient, subject II Tn. I still likes to be lazy so he still needs treatment, the two research subjects know about the type, content, duration, frequency, duration and trigger factors of hallucinations, and are able to independently control hallucinations using SP 1-4 hallucinations. The researcher hopes that further research regarding Mental Nursing Care in Patients with Auditory Hallucinations Nursing Problems can be further developed